2002
DOI: 10.1021/ja017073i
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies To Understand Surface Chemistry on Carbon Anodes for Lithium-Ion Batteries:  How Does Vinylene Carbonate Play Its Role as an Electrolyte Additive?

Abstract: To elucidate the role of vinylene carbonate (VC) as a solvent additive in organic polar solutions for lithium-ion batteries, reductive decompositions for vinylene carbonate (VC) and ethylene carbonate (EC) molecules have been comprehensively investigated both in the gas phase and in solution by means of density functional theory calculations. The salt and solvent effects are incorporated with the clusters (EC)nLi+(VC) (n = 0-3), and further corrections that account for bulk solvent effects are added using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
260
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(267 citation statements)
references
References 22 publications
5
260
2
Order By: Relevance
“…15 Enhanced chemical stability against electrolyte oxidation and reduction, high ionic conductivity, high boiling points, and low melting points are required, as well as the ability to solvate a wide range of lithium salts such as LiPF 6 , LiBF 4 or LiClO 4 , [16][17][18][19][20][21] in aprotic and organic solvents such as ethylene carbonate (EC), propylene carbonate (PC), their mixtures, and ionic liquids. The decomposition mechanism of organic solvent and subsequent formation of SEI films near the graphite anode is a major research topic in lithium ion batteries from theoretical [22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34][35][36][37][38][39] standpoints, and one of the least understood.…”
mentioning
confidence: 99%
“…15 Enhanced chemical stability against electrolyte oxidation and reduction, high ionic conductivity, high boiling points, and low melting points are required, as well as the ability to solvate a wide range of lithium salts such as LiPF 6 , LiBF 4 or LiClO 4 , [16][17][18][19][20][21] in aprotic and organic solvents such as ethylene carbonate (EC), propylene carbonate (PC), their mixtures, and ionic liquids. The decomposition mechanism of organic solvent and subsequent formation of SEI films near the graphite anode is a major research topic in lithium ion batteries from theoretical [22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34][35][36][37][38][39] standpoints, and one of the least understood.…”
mentioning
confidence: 99%
“…Examples are ethylene sulfite [4], and the unsaturated carbonates vinylene carbonate (VC) [5][6][7][8][9][10] and vinyl ethylene carbonate (VEC) [11][12]. The electrochemical reduction of both VC and VEC has been studied in some detail, including quantum chemical calculations of the energetics that identified the most probable reaction pathway [13][14]. Both VC and VEC appear to be reduced at potentials above 1.0 V (vs. Li/Li + ) and form a passivating film that prevents solvent cointercalation and exfoliation of the graphite at lower potentials [6][7]11].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] It has been demonstrated that electrons would be initially transferred from the polarized electrode to the Li + -coordinated solvent (or additive) molecules, forming ion-pair intermediates. Then, a ring-opening would take place on the intermediates to generate radical anions, which participate in termination reactions resulting in proper products in the form of Li organic or inorganic salts, building up the SEI film.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a ring-opening would take place on the intermediates to generate radical anions, which participate in termination reactions resulting in proper products in the form of Li organic or inorganic salts, building up the SEI film. [17][18][19][20][21][22] The elucidation of reaction mechanisms is a major challenge for theoretical studies. To date, many theoreticians have used quantum chemical methods to gain insights into the initial reactions at the microscopic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation